Effect of familiarity and mixing method on gestating sow welfare and productivity in large dynamic groups() - Pierdon, Meghann K (J Anim Sci, 2018)
The objectives of this study were twofold: first, to investigate the effects of sow familiarity prior to mixing into a larger dynamic group of gestating sows and, second, to examine the impact of how the sows entered the pen during this mixing event. The cohort of sows was either familiar with each other because of premixing (PMIX) or unfamiliar (UMIX). This PMIX or containment of sows in a stall (UMIX), occurred from weaning until the sows were mixed into the large gestation pen 8 d later. The cohort of incoming sows was introduced either as a batched unit (BAT) or new sows were introduced into the dynamic group singly (IND) though the electronic sow feeder. Lesion severity and quantity score, lameness, and body condition score (BCS) were tracked throughout the entire gestation period for 213 sows. Overall, there was little effect of the treatment but a strong impact of parity on the outcomes. Younger animals had significantly higher risk for lesions (P < 0.001) and higher risk for more severe lesions (P < 0.001) than higher parity animals. Lower parity had an association with the risk of lameness (P < 0.05), but it had no significant effect on BCS (P > 0.05). The risk of lameness increased on days 15 and 62 compared to weaning (P < 0.001). Risk of low BCS decreased on days 62 and 113 relative to scores at weaning (P < 0.001). A degree of familiarity by day interaction was present for lesion quantity (P < 0.001) and lesion severity (P < 0.001). The risk of more lesions was higher in the premixed groups before going into the dynamic group, but equilibrated with the unmixed group after day 11, 3 d in the large dynamic pen. The highest risk for the greatest quantity of lesions peaked at day 11 then declined, but never reached the lowest level again which was measured at weaning. Despite the variability in the welfare measures, there was no significant impact of treatment or parity on sow productivity. In conclusion, our data demonstrate that a period of premixing sows and varying the method of entering sows into the pen did not have a long-term impact on the welfare of the sows or on their productivity.